The market for borrowing stock - D’Avolio, Gene (Journal of Financial Economics, 2002)
To short a stock, an arbitrageur must first borrow it. This paper describes the market for borrowing and lending U.S. equities, emphasizing the conditions generating and sustaining short-sale constraints. A large institutional lending intermediary provided eighteen months (4/2000–9/2001) of data on loan supply (“shortability”), loan fees (“specialness”), and loan recalls. The data suggest that while loan market specials and recalls are rare on average, the incidence of these short-sale constraints is increasing in the divergence of opinion among investors. Beyond some threshold, investor optimism itself can limit arbitrage via the loan market mechanism.